Emerging Issues in Promoting Competition Policy in the APEC and ASEAN Countries - Rafaelita M. Aldaba (Philippine Institute for Development Studies (PIDS), 2008)
This paper looks at the emerging issues and problems in promoting competition policy and coordinating its implementation under regional arrangements, particularly the APEC and the ASEAN. Implementing competition policy is a big challenge. As the review of country experiences shows, administrative, legal, political, and economic factors are important in the design and implementation of competition law and policy. The APEC experience illustrates that with the wide differences in the countries stage of socioeconomic development as well as in their legal institutions, countries have differed in their approaches to competition. In the ASEAN, difficulties in the development of competition policy are encountered due to the lack of a culture of competition and weak legal and regulatory infrastructures.
Keywords: 330; competition policy; ASEAN; APEC countries; Regionale Wirtschaftsintegration; Wettbewerbspolitik; Internationale Wirtschaftspolitik; APEC-Staaten; ASEAN-Staaten